Estimate of Heritability for some semen traits of White Leghorn - Al-Janabi, Thamer Kareem (Journal of Kerbala for Agricultural Sciences, 2013)
This study was conducted at the Poultry farm / animal resource department , college of A griculture ,Baghdad University , and over the Period form 15-10- 2004 until 30-9-2005 .The aim of this study was estimated heritability of some semen traits by used half-sib Paternal Procedure throw variance and co-variance (VCV) matrix for sire and error , 24 roosters , 144 hens and 193 offspring were used in this experiment . Results obtained can be summarized as follows : The overall means for The semen Volume , Packed semen Volume , mass motility , individual motility , percentage of dead spermatozoa and percentage of abnormal spermatozoa were 0.31 ml , 9.29% , 72.13%, 76.56% , 11.14% and 10.01 % . -Heritability of semen Volume , Packed semen Volume ,mass motility ,individual motility, Percentage of dead spermatozoa and Percentage of abnormal spermatozoa were 0.31 , 023 , 0,26 , 0.27 , 0.29 and 0.26